2011
DOI: 10.1111/j.1478-3231.2011.02453.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis and insulin resistance are associated with severe fibrosis in patients with chronic hepatitis caused by HBV or HCV infection

Abstract: Background and aims: Steatosis and insulin resistance (IR) are the major disease modifying in patients with chronic hepatitis C (CHC). Only few studies evaluated these features in patients with chronic hepatitis B (CHB). We aimed to assess the prevalence and the factors related to steatosis and IR in CHB patients, compared with CHC subjects, and to evaluate the potential association between these features and fibrosis severity. Material and methods: One hundred and seventy consecutive patients with CHB (28 HBe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 56 publications
3
61
1
Order By: Relevance
“…Likewise, in other reports, no significant association was found between the stage of fibrosis and the severity of steatosis (Bondini et al, 2007;Peng et al, 2008;Rastogi et al, 2011). However, by univariate analysis, when the cut off of >3 was used as criterion decision for severe fibrosis, a strong relationship between fibrosis and HS was achieved (p=0.026), a finding similar to two reports (Shi et al, 2008;Petta et al, 2011). Moreover, on multivariate analysis when we compared the HIA scores with the stages of fibrosis in both groups of patients, higher stages of fibrosis (>3) were associated with HAI scores of necroinflammation (P value<0.001), consistent with other reports of patients with CHC and CHB (Altlparmak et al, 2005;Peng et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, in other reports, no significant association was found between the stage of fibrosis and the severity of steatosis (Bondini et al, 2007;Peng et al, 2008;Rastogi et al, 2011). However, by univariate analysis, when the cut off of >3 was used as criterion decision for severe fibrosis, a strong relationship between fibrosis and HS was achieved (p=0.026), a finding similar to two reports (Shi et al, 2008;Petta et al, 2011). Moreover, on multivariate analysis when we compared the HIA scores with the stages of fibrosis in both groups of patients, higher stages of fibrosis (>3) were associated with HAI scores of necroinflammation (P value<0.001), consistent with other reports of patients with CHC and CHB (Altlparmak et al, 2005;Peng et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…168 Coexistent hepatic steatosis is common in chronic hepatitis C (HCV) infection and is strongly associated with more advanced liver disease. [169][170][171] Another large study showed high prevalence of steatosis (40.5%) and steatohepatitis (15%) in patients with primary biliary cirrhosis (PBC), 172 although at least some of the steatosis and steatohepatitis in that study was suspected to be due to alcohol consumption. In clinical practice, it is not uncommon for obese and/or diabetic patients with autoimmune liver disease to exhibit steatosis and steatohepatitis in their liver biopsies.…”
Section: Bariatric Surgerymentioning
confidence: 96%
“…Traditional diagnosis and grading of steatosis requires liver biopsy, with the key distinction between mild and moderate disease generally corresponding to 30-33% fat content at histopathology [13][14][15]. Greater degrees of steatosis have been shown to correlate with worse outcomes in the setting of liver resection, transplantation, and hepatitis C and B virus [14,16,17]. However, although the presence and severity of nonalcoholic steatohepatitis (NASH) and, in particular, the degree of fibrosis portend a worse prognosis in NAFLD [18,19], the natural history of incidental hepatic steatosis, including its actual risk of progression to fibrosis/ cirrhosis and the risk of cardiovascular events, is not well established.…”
Section: Introductionmentioning
confidence: 99%